2015
DOI: 10.1002/app.43344
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun plasma‐modified chitosan/poly(ethylene terephthalate)/ferrocenyl‐substituted N‐acetyl‐2‐pyrazoline fibers for phosphate anion sensing

Abstract: Two ferrocenyl‐substituted N‐acetyl‐2‐pyrazolines, N‐acetyl‐3‐(2‐furyl)‐5‐ferrocenyl‐2‐pyrazoline (Fc‐1) and N‐acetyl‐3‐(2‐thienyl)‐5‐ferrocenyl‐2‐pyrazoline (Fc‐2) electrospun fibers, were produced in the presence of plasma‐modified chitosan (PMCh)/poly(ethylene terephthalate) (PET) supporting polymers with an electrospinning method. The morphological and chemical characterizations of the PMCh/PET/Fc‐1 and PMCh/PET/Fc‐2 electrospun fibers were determined by scanning electron microscopy coupled with energy‐dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The polymer electrospinning spinnability is affected by the polymer solubility, solvent concentration and conductivity, applied voltage and so on 55 . The previous studies showed that a higher applied voltage increased the net charge experienced by the jet, resulting in enhanced fiber drawing to narrow diameters 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer electrospinning spinnability is affected by the polymer solubility, solvent concentration and conductivity, applied voltage and so on 55 . The previous studies showed that a higher applied voltage increased the net charge experienced by the jet, resulting in enhanced fiber drawing to narrow diameters 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies showed that a higher applied voltage increased the net charge experienced by the jet, resulting in enhanced fiber drawing to narrow diameters 39 . Meanwhile, the solvent volatilized quickly in electrospun processing, the appropriate parameters of polymer concentration, applied potential and, working distance are critical factors for optimized nanofibers 39,55 . SEM results for the nanofibers produced from multi‐block copolymers solution are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ITO coated with P2 fibers indicated good reversible redox behavior at E1/2=0.62 V (E1/2 called as half-wave potential for a reversible redox couple (at 25 o C)) for the 0.005 M PBS media. The substitution effect of thiophene on electrochemical properties was studied (Nohut Maslakci et al, 2016). In addition, electroactivity increased with an increase in the amount of polythiophene in the fiber (Can et al, 1998;Kiani et al, 2008;Bertuoli et al, 2019).…”
Section: Electrochemical Resultsmentioning
confidence: 99%
“…Amongst the numerous organic luminescent materials, pyrazoline and its derivatives have received increasing attention due to their excellent electro-optical properties and wide range of applications [5][6][7][8][9][10]. In the past decades, although extensive research has focused on the photophysical properties of 1,3,5-triaryl-substituted pyrazolines [11,12], 1-acetyl-pyrazoline derivatives have also attracted a lot of attention because they have many unique advantages [13]. For example, a large number of 1-acetyl-pyrazoline derivatives show high sensitivity and selectivity towards different metal ions and can be used as fluorescent sensors [14].…”
Section: Introductionmentioning
confidence: 99%